Perfil das gestantes atendidas no ambulatório de medicina materno-fetal da MEAC com cardiopatia e gestação e sua correlação com desfechos maternos e perinatais - Daniel, Elana Couto de Alencar (2024)
Cardio-obstetrics emerges as an important line of study within cardiology due to the increase in maternal morbidity and mortality related to cardiovascular diseases. This occurs both due to the increase in maternal age and the possibility of heart disease patients, who were previously unable to get pregnant, now being able to have offspring. Therefore, a cross-sectional and single-center study was proposed that aims to evaluate the profile of pregnant women treated at the maternal-fetal medicine outpatient clinic with heart disease and pregnancy in a reference maternity hospital, seeking to identify the relationship between maternal and perinatal outcomes with the variables studied. All pregnant women who had their first appointment from January to June 2022 were included, so that the delivery occurred by December 2022, in order to evaluate maternal and perinatal outcomes. It was noticed that the demographic profile of pregnant women has changed a lot in recent decades, with an increase in women who were overweight/obese at the time of conception. Another point worth highlighting is the average age of patients at birth, around 31.95 years, many of whom had comorbidities, such as systemic arterial hypertension and diabetes mellitus. Valvular disease stood out as a cardiovascular disease that affects women of childbearing age, with decompensated valvular heart disease being the main reason for referral to the intensive care unit. The illness that presented the highest prevalence in the present study was hypertensive syndrome. Pre-eclampsia was related to worse maternal and perinatal outcomes. It is noteworthy that cardiovascular disease is the main cause of non-obstetric maternal death and must be managed precisely, ideally by a multidisciplinary team.